2013
DOI: 10.1063/1.4802496
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz intersubband transition in GaN/AlGaN step quantum well

Abstract: The influences of polarization and structure parameters on the intersubband transition frequency within terahertz (THz) range and oscillator strength in GaN/AlGaN step quantum well have been investigated by solving Schrödinger and Poisson equations self-consistently. The results show that the Al mole compositions of step quantum well and space barrier have a significant effect on the THz intersubband transition frequency. A specific phenomenon is found that the minimum energy spacing between the ground state a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Machhadani et al proposed a way to decrease the effect of the internal electric field by creating a 3‐layer well (step‐QW) with a virtually flat potential profile. This approach has been explored by Wu et al , who found that the creating this flat band structure is very sensitive to small changes in aluminum concentration and well depth. Despite these deficiencies, ISB transitions in the THz region have been reported , and a QW infrared photodetector has been demonstrated .…”
Section: Introductionmentioning
confidence: 99%
“…Machhadani et al proposed a way to decrease the effect of the internal electric field by creating a 3‐layer well (step‐QW) with a virtually flat potential profile. This approach has been explored by Wu et al , who found that the creating this flat band structure is very sensitive to small changes in aluminum concentration and well depth. Despite these deficiencies, ISB transitions in the THz region have been reported , and a QW infrared photodetector has been demonstrated .…”
Section: Introductionmentioning
confidence: 99%
“…9,12 However, the transition energies of these step-wells are highly sensitive to structural parameters. 13,14 Moreover, the additional layers significantly increase the complexity of design and growth of practical devices. The challenges of the built-in polarization fields can be circumvented by utilizing non-polar nitride heterostructures.…”
mentioning
confidence: 99%
“…For example, the effects of the intense laser field, indium composition and the well width on the Electron Raman Scattering of the strained InGaN/GaN quantum wells, considering which the spontaneous polarization fields caused by the crystal structure can produce a strong internal built-in electric field [24], the coupled quantum wells and the interaction between the interface related Rashba and Dresselhaus spin-orbit interaction [25], the influences of polarization and structure parameters on the intersubband transition frequency within terahertz range and oscillator strength in GaN/AlGaN step quantum well and other factors including doping location and concentration [15], the properties of AlGaN-based multi-quantumwells designed for intersubband optoelectronics in the THz spectral range. The authors studied the reproducibility issues associated to the current step-QW architecture [26], the intersubband transitions in III-nitride semiconductor [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, semiconductor step-quantum well and multiple quantum wells have aroused great interest because these systems allow the development of light sources such as light emitting diodes and laser diodes in a wide range of the electromagnetic spectrum from terahertz to ultraviolet and far-infrared [9][10][11][12][13][14], secure communication, genetic analysis, biomedical sensing, explosive and drug detection, security screening, industrial process control, and spectroscopic imaging for astronomy and space physics [15,16]. The structure of the step-quantum well and multiple quantum wells is capable of improving the photoluminescence efficiency due to quantum confinement effect.…”
Section: Introductionmentioning
confidence: 99%